2005
DOI: 10.4049/jimmunol.175.4.2666
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Estrogen Receptor Modulators, Tamoxifen and Raloxifene, Impair Dendritic Cell Differentiation and Activation

Abstract: Most immune cells, including myeloid progenitors and terminally differentiated dendritic cells (DC), express estrogen receptors (ER) making these cells sensitive to estrogens. Our laboratory recently demonstrated that 17-β-estradiol (E2) promotes the GM-CSF-mediated development of CD11c+CD11bint DC from murine bone marrow precursors. We tested whether the therapeutic selective estrogen receptor modulators (SERM), raloxifene and tamoxifen, can perturb DC development and activation. SERM, used in treatment of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 57 publications
4
72
1
Order By: Relevance
“…It is plausible, however, that ongoing adjuvant anti-oestrogen therapy may have had an effect on the prolonged decrease in peripheral DC in these patients. In fact, it has been shown that anti-estrogens (such as Tamoxifen) inhibit the in vitro functional differentiation of human monocytes (Komi and Lassila, 2000), synovial macrophages (Komi et al, 2001) and murine splenic monocytes (Nalbandian et al, 2005) into DC, and affect basic immunological functions such as cytokine and chemokine expression (Bengtsson et al, 2004). However, there is no evidence as yet to suggest blood DC levels are affected by oestrogen inhibitors in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…It is plausible, however, that ongoing adjuvant anti-oestrogen therapy may have had an effect on the prolonged decrease in peripheral DC in these patients. In fact, it has been shown that anti-estrogens (such as Tamoxifen) inhibit the in vitro functional differentiation of human monocytes (Komi and Lassila, 2000), synovial macrophages (Komi et al, 2001) and murine splenic monocytes (Nalbandian et al, 2005) into DC, and affect basic immunological functions such as cytokine and chemokine expression (Bengtsson et al, 2004). However, there is no evidence as yet to suggest blood DC levels are affected by oestrogen inhibitors in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…TLR4 is the TLR responsive to LPS. Interestingly, the level of surface TLR4 expression was lower on the CD11b int Ly6C Ϫ DC, indicating that the level of TLR4 expression does not correlate with the extent of LPS-responsiveness (30).…”
Section: Resultsmentioning
confidence: 99%
“…Our experiments with the ER antagonist ICI 182,780, selective ER modulators, and ER␣ Ϫ/Ϫ BM cells indicated that estrogen acts via the ER to promote DC differentiation (29,30 …”
Section: Angerhans Cells (Lc)mentioning
confidence: 99%
“…Similarly, vinblastine was found to promote DCmediated antigen presentation and tumor antigen-specific Tcell responses in vitro and in tumor-bearing hosts (15,16). In contrast, other cytotoxic drugs may block DC maturation, thereby antagonizing antitumor immunity (34,35). Yet, the mechanism proposed here seems to be distinct from direct effects on DCs that have been described using low noncytotoxic concentrations of other classes of cytotoxic drugs (36).…”
Section: Discussionmentioning
confidence: 99%